Determinan Adopsi E-Commerce dan Dampaknya Pada Kinerja Usaha Mikro Kecil Menengah (UMKM) - Nurlinda, Nurlinda -; Fathimah, Vidya (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. This study investigates the determinants of e-Commerce adoption as well as their impact to the performance of MSMEs in Medan City. This research is a quantitative study using primary data collected through surveys with questionnaires. The sample technique used is random sampling resulting in 222 respondents. Empirical model is estimated using regression. Results show that all constructs simultaneously influence e-commerce adoption and e-adoption have a significant positive effect on performance improvement. Partially, organizational willingness and technological willingness have a significant and positive effect on e-commerce adoption, while the external environment has a positive but not significant on improving the performance of MSMEs in Medan City. This research contributes to provide input and description related to the adoption of e-commerce adoption. It can be used as a basis for removing barriers to e-commerce utilization which then could improve performance of MSMEs. Improving financial performance which is one element of performance eventually lead to increasing in profits. Keywords. Adoption of Information Technology; Micro Small and Medium Enterprises; MSMEs; Online Business. Abstrak. Penelitian ini menguji determinan adopsi e-Commerce serta dampaknya pada peningkatan kinerja pada UMKM di Kota Medan. Penelitian ini merupakan penelitian kuantitatif menggunakan data primer yang dikumpulkan melalui survey dengan kuisioner. Teknik sampel menggunakan random sampling sebanyak 222 responden. Model empiris diuji dengan menggunakan regresi. Hasil penelitian menunjukkan secara serempak seluruh konstruk berpengaruh pada adopsi e-commerce dan adopsi e-commerce berpengaruh positif dan signifikan pada peningkatan kinerja. Secara parsial kesediaan organisasi dan kesediaan teknologi berpengaruh positif signifikan terhadap adopsi e-commerce, sedangkan lingkungan eksternal berpengaruh positif namun tidak signifikan terhadap peningkatan kinerja UMKM di Kota Medan. Penelitian berkontribusi untuk memberikan masukan dan gambaran terkait diterminan adopsi e-commerce. Ini akan menjadi dasar dalam menghilangkan penghambat dalam pemanfaatan e-commerce yang kemudian dapat meningkatkan kinerja UMKM. Peningkatan kinerja keuangan yang merupakan salah satu unsur kinerja yang akan meningkatkan laba.